Magnit PJSC stocks: to sell, to buy or to hold - J. A. Konopleva; O. N. Pakova; I. R. Temirbulatova (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. In modern world many people are familiar with the concepts “a stock”, “quotes” and “investment portfolio”. In order to find out the volatility of a security of a particular company, one does not have to be an analyst. The investment portfolio is assembled based on charts, quotes, and profit forecasts.Goal. The study of the results of Magnit PJSC activities, which may lead to a deeper analysis of the investment environment of the company.Materials and methods. The methods of comparison, analysis and synthesis, computational and constructive method, the method of groupings, economic and statistical methods were used.Results and discussion. To accurately predict the success of investing in the securities of the company, it is necessary to study the official financial reports that are publicly available, follow conferences, study articles and any other relevant public mentions of the company and its results. In addition, an important factor is the study of the customers of the company themselves, their reviews and flows.Conclusion. Based on the results of the conducted research and after a thorough analysis of the financial results of the company, a choice should be made in favor of one of three outcomes, namely to sell, to buy or to hold the stocks.